ORGANIZATIONAL STRUCTURE APPROACH TO ORIGINAL REGIONAL INCOME: AN ANALYSIS REVIEW IN BONDOWOSO REGENCY - Susilowati; Diyah Probowulan; Sanosra, Abadi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: PAD is the main source of regional financing to support government administration and development at the regional level. The reason why research on PAD is important is to measure regional financial independence, assess local economic potential, assess the impact of policies and programs and to increase transparency and accountability. Method: The research method used is descriptive qualitative research with a case study approach and literature review. Results: there has been overlapping of duties and functions between fields, namely in the Tax and Levy Sector as well as the PBB P2 and BPHTB Sector, (2) not yet optimal in terms of planning and policy, (3) not yet optimal in digital databases (4) not yet optimal in management and coaching retribution; (5) there is no field that specifically handles inspection and enforcement Novelty: To fill the gap in research regarding PAD revenues related to organizational structure, the author focuses on analyzing reviews of organizational structure approaches to Regional Original Income, with the hope that this can provide useful insights for policy making in regional government and enrich existing literature regarding PAD management.